Pengaruh Pemberian Isometric Exercise Terhadap Peningkatan Fungsional Pada Pasien Osteoarthritis Genu Pada Lansia di Instalasi Rehabilitasi Medik Rumah Sakit Gotong Royong Surabaya - Rizky Apriyanto; Ahmad Abdullah; Rachma Putri Kasimbara; Johanes Deo Fau (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The gotong royong hospital has many elderly patients were almost 40% of the cases they suffer from are osteoarthritis. Osteoarthritis is the most dominant degenerative joint disease in the elderly, accounting for 7.3% of the total disease (Riskesdas 2018). the prevalence of osteoarthritis was 5% under 40 years, 30% between 40-60 years, and 65% over 61 years. According to data from the East Java Health Office, the prevalence of Genu OA customers. (Ministry of Health, 2012: 40)Methods: This study is important to determine the effect of isometric exercise therapy on increasing functional activity in elderly patients with osteoarthritis genu. This research is an experimental research using One Group Pretest and Posttest. The sample population of this study were 20 patients with a diagnosis of osteoarthritis who met the inclusion and exclusion criteria, in treatment at a medical rehabilitation facility.Results: Measurement with the WOMAC index then obtained the value of functional activity at the beginning of the assessment before the intervention was carried out, the mean value was 33.51. Then the measurement after being given isometric exercise intervention obtained WOMAC value, namely the mean value of 23.63. The paired sample t-test was continued with the paired sample t-test results showing a significant number between the pre and post-test values with a significance value (2-tailed) p = 0.000, <0.05 (see table). The null hypothesis (H0) in this study was rejected and the alternative hypothesis was accepted where there was a significant difference between the two tests.Conclusion: There is an effect of isometric exercise on increasing the functional ability of the elderly with osteoarthritis in the medical rehabilitation installation of the Gotong Royong Hospital in Surabaya.